The History and Development of Latin Language Education from the Late 19th to the Early 21st Centuries - Walsh, John (Nouvelle Revue Synergies Canada, 2025)
Historically, Classical Latin had a fundamental role in the history of Western education systems. This paper examines the teaching of Latin over the past 150 years in the US, Britain, and Australia and demonstrates how Latin teaching has moved in step with complex social changes during the history of modern education. A conclusion follows that evaluates methods of delivering Latin language education to meet student and institutional expected learning outcomes in a modern climate of pedagogical reform, technological innovation, and social development.